2023
DOI: 10.3390/ijpb14020031
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sources of Resistance to Stagonospora nodorum and Role of Effector-Susceptibility Gene Interactions in Wheat of Russian Breeding

Abstract: Virulence factors of the pathogen Stagonospora nodorum Berk. are numerous necrotrophic effectors (NEs) (SnTox), which interact with the products of host susceptibility genes (Snn), causing the development of the disease. In this study, 55 accessions of bread spring and winter wheat were screened for sensitivity to NEs SnToxA, SnTox1, and SnTox3 using different isolates of S. nodorum. In the studied panel of wheat, 47 accessions were modern commercial cultivars grown in Russia and 8 cultivars were historic whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(128 reference statements)
1
2
0
Order By: Relevance
“…It was previously shown that the virulence of S. nodorum strains depends on the level of expression of NE genes [26,27,30,47,48]. Isolates SnB, Sn4VD and Sn9MN-3A studied in this work had different virulence [32,33], and as our results showed, they differed in the pattern of expression of NE genes (Figure 6). Isolates SnB and Sn9MN-3A were characterized by higher expression of the SnToxA and SnTox3 genes compared to the avirulent isolate Sn4VD (Figure 6).…”
Section: The Influence Of Cks and Aba On The Growth And Sporulation O...supporting
confidence: 59%
See 1 more Smart Citation
“…It was previously shown that the virulence of S. nodorum strains depends on the level of expression of NE genes [26,27,30,47,48]. Isolates SnB, Sn4VD and Sn9MN-3A studied in this work had different virulence [32,33], and as our results showed, they differed in the pattern of expression of NE genes (Figure 6). Isolates SnB and Sn9MN-3A were characterized by higher expression of the SnToxA and SnTox3 genes compared to the avirulent isolate Sn4VD (Figure 6).…”
Section: The Influence Of Cks and Aba On The Growth And Sporulation O...supporting
confidence: 59%
“…Previously, we showed that isolates of S. nodorum SnB and Sn9MN-3A contain SnToxA and SnTox3 in their genome sequences of NEs, and these isolates are virulent against wheat genotypes carrying the corresponding susceptibility genes complementary to these effectors [32,33]. The S. nodorum Sn4VD isolate contained in its genome the genes encoding three NEs: SnTox1, SnToxA and SnTox3, but the Sn4VD isolate was avirulent and weakly infected susceptible wheat genotypes [32].…”
Section: Introductionmentioning
confidence: 98%
“…Only genes for resistance to Bgt Pm12 , PmSp , and PmKu were described as effective against the pathogen populations from the northwestern part of the Russian Federation [ 29 , 30 , 58 ], but samples with these genes were found to be susceptible in 2022 [ 21 ]. Several varieties of bread wheat were evaluated as resistant to HLB [ 56 , 59 ] and SNB [ 60 , 61 ], but their re-evaluation showed their susceptibility (not published). Only four genes for yellow rust resistance ( Yr5 , Yr10 , Yr15 , and Yr24 ) have been described as effective against Pst in Russia [ 31 ].…”
Section: Discussionmentioning
confidence: 99%